2022
DOI: 10.11606/s1518-8787.2022056003839
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A and E among immigrants and refugees in Central Brazil

Abstract: OBJECTIVE To estimate the prevalence of hepatitis A virus (HAV) and hepatitis E virus (HEV) among immigrants and refugees in Goiás, Central Brazil. METHODS Overall, 355 individuals were interviewed, and blood samples were tested for anti-HAV and anti-HEV IgG. Anti-HEV-positive samples were similarly tested for HEV RNA. RESULTS All participants were from Latin American countries, most of whom, young adult males. The overall anti-HAV IgG prevalence was 87.4% (95%CI: 83.5–90.4), of whom 94.9%, 75.6%, and 60% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…This low HEV seroprevalence found is also in line with the few studies performed in children in Latin America [ 3 ]. Some of them documented prevalences of 1.2 % in Chile [ 15 ], 1.7 % in Bolivia [ 16 ], 1.1 % in Colombia [ 3 ] and 1.6 % in Brazil [ 17 ], while others reported slightly higher seroprevalence rates of 4.5 % in Mato Grosso State in Brazil [ 18 ], or 3 % and 3.9 % in Mexico [ 19 , 20 ]. Although the different diagnostic kits used could be a factor of variability in the reported prevalences, in all studies low circulation values were recorded in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…This low HEV seroprevalence found is also in line with the few studies performed in children in Latin America [ 3 ]. Some of them documented prevalences of 1.2 % in Chile [ 15 ], 1.7 % in Bolivia [ 16 ], 1.1 % in Colombia [ 3 ] and 1.6 % in Brazil [ 17 ], while others reported slightly higher seroprevalence rates of 4.5 % in Mato Grosso State in Brazil [ 18 ], or 3 % and 3.9 % in Mexico [ 19 , 20 ]. Although the different diagnostic kits used could be a factor of variability in the reported prevalences, in all studies low circulation values were recorded in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Il n'existe pas de données concernant le Suriname. Concernant Haïti, la séroprévalence a été estimée à 10,3% chez les femmes enceintes et les personnes originaires d'Haïti représentaient l'intégralité des cas séropositifs dans une étude réalisée auprès d'immigrés du centre du Brésil, y compris des enfants nés au Brésil de parents haïtiens (2 de ces cas étaient aussi positifs en ARN VHE, traduisant une infection active) [ 342 , 360 ]. Ainsi, face à cette lacune majeure dans la connaissance sur les hépatites virales à transmission féco-orale A et E, il est impératif de mettre en place des études visant à évaluer leur incidence et leur séroprévalence en Guyane.…”
Section: Pathologies Infectieuses Fébrilesunclassified
“…More recently, in 2017, a study of the Warao indigenous communities of the Orinoco Delta, Venezuela documented a seroprevalence of HBsAg of 1.8% and anti-HBc of 13% [ 14 ]. In 2022, a study of Venezuelan and Haitian migrants and refugees in Brazil reported an anti-HAV immunoglobulin G prevalence of 94.9% in Haitians and 75.6% in Venezuelans aged 19 years and over [ 15 ].…”
Section: Introductionmentioning
confidence: 99%